Analisis Tindak Tutur Representatif dalam Video "Pengantar Sastra Indonesia" pada Saluran YouTube Restu Bias Primandhika - Awalina Putriyani; Dea Nisa Febrianti; Dela Agustin Erika Sari; Ivana Zafirah; Yaffadevi Palastri Marhaeni Putri; Asep Purwo Yudi Utomo; Hidayatun Nur; Molas Warsi Nugraheni (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Representative speech acts are an important aspect in pragmatics that helps understand the application of speech acts, especially in the context of learning videos on digital platforms such as YouTube. This study aims to provide readers, especially students of the Indonesian Language and Literature Education study program, with an understanding of the meaning, various types, and application of representative speech acts contained in the "Pengantar Sastra Indonesia" video on the "Restu Bias Primandhika" YouTube channel. This research sees video not only as a medium of information, but also as a tool that influences the interaction between speakers and listeners. This research uses a pragmatic approach by using a qualitative descriptive method. The data collection technique in this research uses the method of free listening and recording technique, which allows researchers to observe and record speech acts in their original context. The research found 113 representative speeches divided into eight main categories: stating, showing, mentioning, informing, suggesting, explaining, giving examples, and speculating. Of the 113 utterances, there are 16 utterances of stating, 6 utterances of mentioning, 14 utterances of showing, 23 utterances of informing or telling, 17 utterances of suggesting, 18 utterances of explaining, 13 utterances of giving examples, and 6 utterances of speculating. These findings show the various ways speakers use language effectively and persuasively. This study is expected to provide insight for readers regarding representative speech acts and become a reference for further studies in diverse communication contexts.